Bap and Cell Surface Hydrophobicity Are Important Factors in Staphylococcus xylosus Biofilm Formation - Schiffer, Carolin; Hilgarth, Maik; Ehrmann, Matthias; Vogel, Rudi F. (Frontiers in Microbiology, 2019)
Staphylococcus (S.) xylosus is a coagulase-negative Staphylococcus species naturally present in food of animal origin with a previously described potential for biofilm formation. In this study we characterized biofilm formation of five selected strains isolated from raw fermented dry sausages, upon different growth conditions. Four strains exhibited a biofilm positive phenotype with strain-dependent intensities. Biofilm formation of S. xylosus was influenced by the addition of glucose, sodium chloride and lactate to the growth medium, respectively. It was further dependent on strain-specific cell surface properties. Three strains exhibited hydrophobic and two hydrophilic cell surface properties. The biofilm positive hydrophilic strain TMW 2.1523 adhered significantly better to hydrophilic than to hydrophobic supports, whereas the differences in adherence to hydrophobic versus hydrophilic supports were not as distinct for the hydrophobic strains TMW 2.1023, TMW 2.1323, TMW 2.1521. Comparative genomics enabled prediction of functional biofilm-related genes and link these to phenotypic variations. While a wide range of biofilm associated factors/genes previously described for S. aureus and S. epidermidis were absent in the genomes of the five strains analyzed, they all possess the gene encoding biofilm associated protein Bap. The only biofilm negative strain TMW 2.1602 showed a mutation in the bap sequence. This study demonstrates that Bap and surface hydrophobicity are major factors of S. xylosus biofilm formation with potential impact on the assertiveness of a starter strain against autochthonous staphylococci by competitive exclusion during raw sausage fermentation.